A Nationwide Study of Inpatient Case Rate Incidence of Cannabis-Related Diagnoses in Switzerland - Philippe Pfeifer; Reto Auer; Reto Auer; Stéphanie Baggio; Stéphanie Baggio; Franz Moggi (Frontiers Media S.A., 2022)
Objectives: Cannabis is the most commonly used illicit substance and has been associated with mental health issues. In this study, we examined trends in hospitalizations due to cannabis use.Methods: Data were obtained from the Swiss Federal Statistics Office and comprised hospital main diagnoses, gender, age group and region of all psychiatric inpatient cases in Switzerland from 1998 to 2020. We performed trend analyses of annual case rates with cannabinoid-related diagnoses and compared them to trend analyses of alcohol-related and psychotic disorders.Results: Case rates of CRDs significantly increased in the observed time period. From all psychiatric main diagnoses, CRDs were overrepresented in the age groups of 15-24 and 25-44 years.Conclusion: We found a sharp increase in hospitalizations for CRD. Future studies should test whether changes in the upcoming cannabis regulation, which can facilitate the implementation of interventions to address mental health among users, impact future hospitalization rates of CRD.